Autonomic computing systems utilizing agents for risk mitigation of IT governance - Anthony Jnr, Bokolo; Che Pa, Noraini; Mohd Aris, Teh Noranis; Nor, Rozi Nor Haizan; Jusoh, Yusmadi Yah (Penerbit UTM Press, 2015)
Risk mitigation has gained relevance during the last years and has helped to solve risk and improve decision making among decision makers in IT Governance. However, there is still a increasing need of developing innovative tools that can help IT Practitioners to solve risk in IT Governance. Existing risk mitigation approaches or tools lacks need for adequate data which is very important in mitigating risk and there is difficulty of mitigating risk generally in IT Governance. This paper present an autonomic computing model developed to mitigate risk; mainly operational and technical in IT Governance by measuring the risk and providing risk report to the management and staffs in organisations. Autonomic Computing Systems (ACSs) are systems that manage themselves. The core of Autonomic Computing Systems are type of agent with advanced capacities for reasoning to measure the risk probability and risk impact based on available data in the knowledge base or previous experiences. The Autonomic Computing Systems provide risk advice aimed at providing decision support to management hence mitigating risk in IT Governance. Data was collected via purposely sampling using interview by case study among 13 Malaysia universities. The data was analyzed by Nvivo to get an insight on the current risk mitigation practices and process, after which a risk mitigation model has been developed using autonomic agents.